Moderate Alcoholic Beer Consumption: The Effects on the Lipid Profile and Insulin Sensitivity of Adult Men. Issue 7 (16th June 2017) - Nogueira, Luciana C.; do Rio, Rafaela F.; Lollo, Pablo C. B.; Ferreira, Isabel M.P.L.V.O.
Abstract: Beer is the most consumed alcoholic beverage in the world. The purpose was to compare the effects of consuming alcoholic beer (AB) and nonalcoholic beer (NAB) on the biochemical blood parameters. Two beers were produced under known and controlled conditions from the same raw material, NAB (0.6%, v/v) and AB with the addition of 6% grain alcohol. Fifteen healthy adult men (aged 20 to 57 y) underwent 3 treatments (30 d per treatment). In Treatment 1 (Baseline), they followed their usual diet without drinking any alcoholic beverage; in Treatment 2, they added the daily consumption of 330 mL NAB; and in Treatment 3, they added the daily consumption of 330 mL AB. It was found that the use of AB for 30 d (16 g alcohol/d) reduced the blood insulin and fasting glucose, reducing insulin resistance. These data suggest that the daily intake of 330 mL AB could statistically change the lipid profile and insulin sensitivity of adult men. The volunteers were healthy before and remained so after the intervention, with no change in their clinical status.